GPU Computing to Improve Game Engine Performance - Abu Asaduzzaman; Hin Y. Lee (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
Although the graphics processing unit (GPU) was originally designed to accelerate the image creation for output to display, today's general purpose GPU (GPGPU) computing offers unprecedented performance by offloading computing-intensive portions of the application to the GPGPU, while running the remainder of the code on the central processing unit (CPU). The highly parallel structure of a many core GPGPU can process large blocks of data faster using multithreaded concurrent processing. A game engine has many